Exploration of Vision and Language in Education: A Bibliometric Study and Its Implications - I. S. Mannesa, Muh. Nur Haq; Sabriasrifah, Sabriasrifah; Pujhana, I Kadek Wahyu; Koesrohmaniah, Sri; Sulastri, Augustina (Universitas Ibn Khaldun Bogor, 2025)
This research aims to identify the specific contributions of vision and language technology to educational outcomes and to explore how these technologies can be used in current teaching practices. Using bibliometric analysis, clustering, and publications in the field of neuropsychology, this research examines the theoretical relationship between